Preliminary study on simulation of climate change impacts on rice yield using DSSAT 4.5 at Tanjung Karang, Selangor - Shaidatul Azdawiyah, A.T.; Sahibin, A.R.; Anizan, I. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Weather plays a very important role in determining crop yields. There is a strong relationship between climate and crops. The growth requirements are different for every crop throughout the whole plant development process. Each crop and crop variety has specific climatic tolerances and optimal conditions. The objectives of this study were to determine the physico-chemical characteristics of soils for rice cultivation and the effects of climate towards rice yield through simulation using Decision Support System for Agro-technology Transfer ver 4.5 (DSSAT4.5). This study was carried out in Tanjung Karang, Selangor.Four plots with the size of 5 m x 5 m were planted with MR 219 seedlings. Three soil samples were taken from each plot at a depth of 0-20 cm for the upper layer and 20-40 cm for the second layer before planting activities. Physico-chemical characteristic of these soils such as particle size distribution, organic matter, bulk and true density, pH, electrical conductivity, cation exchange capacity and organic carbon contents were determined according to the standard methods. The soil texture in this area was silty clay for the upper layer and clay for the second layer. The percentage of soil organic matter was high at about 9.0% to 11.8%. Soil bulk density was in the range of 1.37 g cm-3 to 1.41 g cm-3, whereas the true density was between 2.5 g cm-3 and 2.75 g cm-3. Soil of this area was slightly acidic with pH value of about 5 to 6. Electrical conductivity recorded ranged from 2.13 mS cm-1 to 2.60 mS cm-1, whereas cation exchange capacity was between 13.5 meq/100 g to 15.5 meq/100 g. Percentage of organic carbon was higher in the upper layer at 2.07-2.74% than in the second layer at 1.25-1.73%. To obtain the yield, ten matured rice plants were randomly selected and harvested. Yield recorded was 5.75 tons ha-1 and the weight of 1000 grains was 24.8 g. Yield simulation by using DSSAT 4.5 crop simulation model, indicated that yield was projected to decrease slightly as the daily solar radiation and rainfall decreased, and slightly increased as the temperature increased.